Multiplex electrochemical sensing platforms for the detection of breast cancer biomarkers - O’Brien, Connor; Khor, Chun Keat; Ardalan, Sina; Ignaszak, Anna (Frontiers in Medical Technology, 2024)
Herein, advancements in electroanalytical devices for the simultaneous detection of diverse breast cancer (BC) markers are demonstrated. This article identifies several important areas of exploration for electrochemical diagnostics and highlights important factors that are pivotal for the successful deployment of novel bioanalytical devices. We have highlighted that the limits of detection (LOD) reported for the multiplex electrochemical biosensor can surpass the sensitivity displayed by current clinical standards such as ELISA, FISH, and PCR. HER-2; a breast cancer marker characterised by increased metastatic potential, more aggressive development, and poor clinical outcomes; can be sensed with a LOD of 0.5 ng/mL using electrochemical multiplex platforms, which falls within the range of that measured by ELISA (from picogram/mL to nanogram/mL). Electrochemical multiplex biosensors are reported with detection limits of 0.53 ng/mL and 0.21 U/mL for MUC-1 and CA 15-3, respectively, or 5.8 × 10 - 3 U/mL for CA 15-3 alone. The sensitivity of electrochemical assays is improved when compared to conventional analysis of MUC-1 protein which is detected at 11-12 ng/mL, and ≤ 30 U/mL for CA 15-3 in the current clinical blood tests. The LOD for micro-ribonucleic acid (miRNA) biomarkers analyzed by electrochemical multiplex assays were all notedly superior at 9.79 × 10 -16